Fault and fracture response to Neogene extension in the western Delaware Basin, Texas - David A. Ferrill; Adam J. Cawood; Kevin J. Smart; Daniel J. Lehrmann; Bethany Rysak Bryce; Mark A. Evans; Lisa D. Stockli; Daniel F. Stockli (Journal of Structural Geology, 2026)

Identification of pesticides and their transformation products in surface water and groundwater surrounding a closed bioethanol production facility using non-targeted analysis - Angela L. Batt; Laura D. Brunelle; Eva K. Stebel; Daniel D. Snow; Esra Mutlu; Antony J. Williams; Gregory Janesch; Caroline Tebes-Stevens; Troy M. Ferland; Shannon Bartelt-Hunt; Judy Wu-Smart (Environmental Pollution, 2025)

Fault zone deformation and fracture intensity in chalk-dominated carbonates - David A. Ferrill; Adam J. Cawood; Kevin J. Smart; Daniel J. Lehrmann; Mark A. Evans; Lisa D. Stockli; Daniel F. Stockli (Journal of Structural Geology, 2025)

Offset integrity reduces environmental risk: Using lessons from biodiversity and carbon offsetting to inform water quality offsetting in the catchments of the Great Barrier Reef - J.M. McMahon; R.D.R. Turner; J.C.R. Smart; J.S. Shortle; I. Ramsay; D.F. Correa; D. Chamberlain; Y. Mao; M.St.J. Warne (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P01-40 Contemporary in vitro toxicology assessment of a novel Herbal Heated Product (HHP) compared to cigarette smoke - E. Bishop; F. Yu; S. Bozhilova; F. Miazzi; Y. Li; L. Smith; D. Smart; D. Breheny (Toxicology Letters, 2024)

Wilder rangelands as a natural climate opportunity: Linking climate action to biodiversity conservation and social transformation - Lavhelesani D. Simba; Mariska te Beest; Heidi-Jayne Hawkins; Keith W. Larson; Anthony R. Palmer; Camilla Sandström; Kathleen G. Smart; Graham I. H. Kerley; Joris P. G. M. Cromsigt (Ambio, 2024)
Rangelands face threats from climate and land-use change, including inappropriate climate change mitigation initiatives such as tree planting in grassy ecosystems. The marginalization and impoverishment of rangeland communities and their indigenous knowledge systems, and the loss of biodiversity and ecosystem services, are additional major challenges. To address these issues, we propose the wilder rangelands integrated framework, co-developed by South African and European scientists from diverse disciplines, as an opportunity to address the climate, livelihood, and biodiversity challenges in the world’s rangelands. More specifically, we present a Theory of Change to guide the design, monitoring, and evaluation of wilder rangelands. Through this, we aim to promote rangeland restoration, where local communities collaborate with regional and international actors to co-create new rangeland use models that simultaneously mitigate the impacts of climate change, restore biodiversity, and improve both ecosystem functioning and livelihoods.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

P16-42: An in vitro toxicological assessment of two electronic cigarettes with differing heating techniologies:e-liquid to aerosolisation - E. Bishop; F. Miazzi; S. Bozhilova; N. East; R. Evans; D. Smart; D. Breheny; M. Gaca; D. Thorne (Toxicology Letters, 2023)

Landuse, landcover change dynamics and flooding in the lower Niger basin Onitsha, South Eastern Nigeria - Ezebube M. Nkiruka; Ani D. Chinedu; Uchegbu N. Smart (Land Use Policy, 2023)

Illegal killing associated with gamebird management accounts for up to three-quarters of annual mortality in Hen Harriers Circus cyaneus - Steven R. Ewing; Cathleen E. Thomas; Nigel Butcher; Blánaid Denman; David J.T. Douglas; David I.K. Anderson; Guy Q.A. Anderson; James Bray; Steve Downing; Ronan Dugan; Brian Etheridge; Will Hayward; et al. (Biological Conservation, 2023)

Transferring Tsyganenko 1989 magnetospheric modulation for cosmic radiation cutoff rigidity values to different epochs of the International geomagnetic reference field - Don F. Smart; Margaret Ann Shea; Paul R. Boberg; Zachary D. Robinson; Jonathan H. Fisher; James H. Adams; Wally D. Westlake (Advances in Space Research, 2023)

Reproductive changes in Foveaux Strait Ostrea chilensis , Southern New Zealand, after Bonamia exitiosa epidemics - Samuel D. Heenan; Keith P. Michael; Daniel C. Smart; P. Mark Lokman; Miles D. Lamare (New Zealand Journal of Marine and Freshwater Research, 2023)
The commercially significant Foveaux Strait Ostrea chilensis fishery has been typified by consistently low brooding rates and recruitment failures since recurrent mass mortalities from Bonamia exitiosa infection. The present study examined the gametogenic cycle of Foveaux Strait O. chilensis monthly, from July 2017 to September 2018, using histological examination of the gonad and condition indices to determine resulting changes to gametogenesis, spawning, brooding, and spatial variation, compared to an initial study of reproduction before B. exitiosa epidemics. The seasonal gametogenic cycle and brooding period were similar to previous descriptions. However, there was evidence for a more female skewed sex ratio, and the development and release of ova into the mantle cavity at smaller sizes. Despite similarities in gametogenesis, sex ratios, temperature, and chlorophyll‐a concentrations between five sites across Foveaux Strait, the western‐most site had no brooders and consistently lower condition indices, compared to the eastern‐most site. Oysters may need to be in sufficient condition to initiate brooding, and reduced male densities may contribute to sperm limitation, which, along with a disconnect between the peak release of gametes and brooding, may have contributed to lower brooding rates.

Water trading by Aboriginal organisations in NSW, Australia - Lana D. Hartwig; Sue Jackson; James C.R. Smart; Natalie Osborne (Journal of Rural Studies, 2023)

Constructed Wetlands Suitability for Sugarcane Profitability, Freshwater Biodiversity and Ecosystem Services - Adam D. Canning; James C. R. Smart; Joshua Dyke; Graeme Curwen; Syezlin Hasan; Nathan J. Waltham (Environmental Management, 2023)
Freshwater ecosystems, such as wetlands, are among the most impacted by agricultural expansion and intensification through extensive drainage and pollution. There is a pressing need to identify ways of managing agricultural landscapes to ensure food and water security without jeopardising biodiversity and other environmental benefits. Here we examine the potential fish biodiversity and landholder financial benefits arising from the integration of constructed lagoons to improve drainage, flow regulation and habitat connectivity within a sugarcane dominated catchment in north Queensland, Australia. A hybrid approach was used, combining the findings of both fish ecological surveys and a financial cost-benefit analysis. We found that the constructed lagoons supported at least 36 native freshwater fishes (over half of all native freshwater fishes in the region), owing to their depth, vegetated margins, moderate water quality and high connectivity to the Tully River. In addition to biodiversity benefits, we estimated that surrounding sugarcane farms would have financially benefited from reduced flooding of cropland and the elevation of low-lying cropland with deposited spoil excavated from lagoon construction. Improved drainage and flow regulation allowed for improvement in sugarcane yield and elevated land increased gross margins from extending the length of the cane production cycle or enabling a switch from cattle grazing to cane production. Restoring or creating wetlands to reduce flooding in flood-prone catchments is a globally applicable model that could improve both agricultural productivity and aquatic biodiversity, while potentially increasing farm income by attracting payments for provision of ecosystem services.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Preliminary age and growth estimates of the blue shark (Prionace glauca) from Papua New Guinea - Sushmita Mukherji; Jonathan Smart; Brooke D’Alberto; Leontine Baje; Andrew Chin; William White; Colin A. Simpfendorfer (Environmental Biology of Fishes, 2021)

Seasonal reproduction of the blue mussel ( Mytilus galloprovincialis ) from two locations in southern New Zealand - Daniel C. Smart; Samuel Heenan; P. Mark Lokman; Miles D. Lamare (New Zealand Journal of Marine and Freshwater Research, 2021)
Blue mussels, Mytilus galloprovincialis, are a widespread and ecologically important species in New Zealand coastal ecosystems, yet, there is limited information on the seasonality and variability in reproduction among populations. The reproductive cycle of M. galloprovincialis was studied monthly over 1‐year in two southern New Zealand populations (Aramoana (45.7787°S, 170.7037°E) and Timaru (44.3905°S, 171.2498°E)). Tissue indices were determined, and gonads examined histologically. At both sites, males and females displayed synchronous changes in condition indices and gonad indices, with both indices generally greater in the Timaru population than in the Aramoana population. Both sampling sites presented with comparable seasonality of reproduction with spawning over spring and summer months (September to February). Gametogenic development occurred over the autumn and early‐winter period (March to August). Spatial differences in reproduction coincided with differences in phytoplankton food abundance (greater in Timaru), while there were only small differences in sea temperatures between sites. This study indicates the likelihood of spatial variation in reproductive biology between M. galloprovincialis populations, even across small spatial scales (

A combined BSA-Seq and linkage mapping approach identifies genomic regions associated with Phytophthora root and crown rot resistance in squash - Gregory Vogel; Kyle E. LaPlant; Michael Mazourek; Michael A. Gore; Christine D. Smart (Theoretical and Applied Genetics, 2021)

Low accuracy of self-reported family history of melanoma in high-risk patients - Nicholas D. Flint; Michael D. Bishop; Tristan C. Smart; Jennifer L. Strunck; Kenneth M. Boucher; Douglas Grossman; Aaron M. Secrest (Familial Cancer, 2021)

A narrative review of the potential pharmacological influence and safety of ibuprofen on coronavirus disease 19 (COVID-19), ACE2, and the immune system: a dichotomy of expectation and reality - Lucinda Smart; Neil Fawkes; Paul Goggin; Graham Pennick; K. D. Rainsford; Bruce Charlesworth; Neil Shah (Inflammopharmacology, 2020)
The coronavirus disease 19 (COVID-19) pandemic is currently the most acute healthcare challenge in the world. Despite growing knowledge of the nature of Severe Acute Respiratory Syndrome coronavirus-2 (SARS-CoV-2), treatment options are still poorly defined. The safety of non-steroidal anti-inflammatory drugs (NSAIDs), specifically ibuprofen, has been openly questioned without any supporting evidence or clarity over dose, duration, or temporality of administration. This has been further conflicted by the initiation of studies to assess the efficacy of ibuprofen in improving outcomes in severe COVID-19 patients. To clarify the scientific reality, a literature search was conducted alongside considerations of the pharmacological properties of ibuprofen in order to construct this narrative review. The literature suggests that double-blind, placebo-controlled study results must be reported and carefully analysed for safety and efficacy in patients with COVID-19 before any recommendations can be made regarding the use of ibuprofen in such patients. Limited studies have suggested: (i) no direct interactions between ibuprofen and SARS-CoV-2 and (ii) there is no evidence to suggest ibuprofen affects the regulation of angiotensin-converting-enzyme 2 (ACE2), the receptor for COVID-19, in human studies. Furthermore, in vitro studies suggest ibuprofen may facilitate cleavage of ACE2 from the membrane, preventing membrane-dependent viral entry into the cell, the clinical significance of which is uncertain. Additionally, in vitro evidence suggests that inhibition of the transcription factor nuclear factor-κB (NF-kB) by ibuprofen may have a role in reducing excess inflammation or cytokine release in COVID-19 patients. Finally, there is no evidence that ibuprofen will aggravate or increase the chance of infection of COVID-19.

Identifying and prioritising adaptation options for a coastal freshwater supply and demand system under climatic and non-climatic changes - Thuc D. Phan; James C. R. Smart; Oz Sahin; Ben Stewart-Koster; Wade L. Hadwen; Samantha J. Capon (Regional Environmental Change, 2020)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Linking residential saltwater intrusion risk perceptions to physical exposure of climate change impacts in rural coastal communities of North Carolina - Abinash Bhattachan; Matthew D. Jurjonas; Priscilla R. Morris; Paul J. Taillie; Lindsey S. Smart; Ryan E. Emanuel; Erin L. Seekamp (Natural Hazards, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Methane and carbon dioxide fluxes from open and blocked ditches in a blanket bog - Sophie M. Green; Andy J. Baird; Chris D. Evans; Mike Peacock; Joseph Holden; Pippa J. Chapman; Richard P. Smart (Plant and Soil, 2018)

Climate change impacts and adaptive strategies: lessons from the grapevine - Jonathan R. Mosedale; Kirsten E. Abernethy; Richard E. Smart; Robert J. Wilson; Ilya M. D. Maclean (Global Change Biology, 2016)
The cultivation of grapevines for winemaking, known as viticulture, is widely cited as a climate‐sensitive agricultural system that has been used as an indicator of both historic and contemporary climate change. Numerous studies have questioned the viability of major viticulture regions under future climate projections. We review the methods used to study the impacts of climate change on viticulture in the light of what is known about the effects of climate and weather on the yields and quality of vineyard harvests. Many potential impacts of climate change on viticulture, particularly those associated with a change in climate variability or seasonal weather patterns, are rarely captured. Key biophysical characteristics of viticulture are often unaccounted for, including the variability of grapevine phenology and the exploitation of microclimatic niches that permit successful cultivation under suboptimal macroclimatic conditions. We consider how these same biophysical characteristics permit a variety of strategies by which viticulture can adapt to changing climatic conditions. The ability to realize these strategies, however, is affected by uneven exposure to risks across the winemaking sector, and the evolving capacity for decision‐making within and across organizational boundaries. The role grape provenance plays in shaping perceptions of wine value and quality illustrates how conflicts of interest influence decisions about adaptive strategies within the industry. We conclude by considering what lessons can be taken from viticulture for studies of climate change impacts and the capacity for adaptation in other agricultural and natural systems.

Legacy effects of grassland management on soil carbon to depth - Susan E. Ward; Simon M. Smart; Helen Quirk; Jerry R. B. Tallowin; Simon R. Mortimer; Robert S. Shiel; Andrew Wilby; Richard D. Bardgett (Global Change Biology, 2016)
The importance of managing land to optimize carbon sequestration for climate change mitigation is widely recognized, with grasslands being identified as having the potential to sequester additional carbon. However, most soil carbon inventories only consider surface soils, and most large‐scale surveys group ecosystems into broad habitats without considering management intensity. Consequently, little is known about the quantity of deep soil carbon and its sensitivity to management. From a nationwide survey of grassland soils to 1 m depth, we show that carbon in grassland soils is vulnerable to management and that these management effects can be detected to considerable depth down the soil profile, albeit at decreasing significance with depth. Carbon concentrations in soil decreased as management intensity increased, but greatest soil carbon stocks (accounting for bulk density differences), were at intermediate levels of management. Our study also highlights the considerable amounts of carbon in subsurface soil below 30 cm, which is missed by standard carbon inventories. We estimate grassland soil carbon in Great Britain to be 2097 Tg C to a depth of 1 m, with ~60% of this carbon being below 30 cm. Total stocks of soil carbon (t ha −1 ) to 1 m depth were 10.7% greater at intermediate relative to intensive management, which equates to 10.1 t ha −1 in surface soils (0–30 cm), and 13.7 t ha −1 in soils from 30 to 100 cm depth. Our findings highlight the existence of substantial carbon stocks at depth in grassland soils that are sensitive to management. This is of high relevance globally, given the extent of land cover and large stocks of carbon held in temperate managed grasslands. Our findings have implications for the future management of grasslands for carbon storage and climate mitigation, and for global carbon models which do not currently account for changes in soil carbon to depth with management.

Ploidy Level Affects Important Biomass Traits of Novel Shrub Willow (Salix) Hybrids - Michelle J. Serapiglia; Fred E. Gouker; J. Foster Hart; Faride Unda; Shawn D. Mansfield; Arthur J. Stipanovic; Lawrence B. Smart (BioEnergy Research, 2015)

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Transformation of Phytophthora capsici with genes for green and red fluorescent protein for use in visualizing plant-pathogen interactions - A. R. Dunn; B. A. Fry; T. Y. Lee; K. D. Conley; V. Balaji; W. E. Fry; A. McLeod; C. D. Smart (Australasian Plant Pathology, 2013)

Yield and Woody Biomass Traits of Novel Shrub Willow Hybrids at Two Contrasting Sites - Michelle J. Serapiglia; Kimberly D. Cameron; Arthur J. Stipanovic; Lawrence P. Abrahamson; Timothy A. Volk; Lawrence B. Smart (BioEnergy Research, 2013)

Estimation of actual evapotranspiration in winegrape vineyards located on hillside terrain using surface renewal analysis - T. M. Shapland; R. L. Snyder; D. R. Smart; L. E. Williams (Irrigation Science, 2012)

Correlations of expression of cell wall biosynthesis genes with variation in biomass composition in shrub willow (Salix spp.) biomass crops - Michelle J. Serapiglia; Kimberly D. Cameron; Arthur J. Stipanovic; Lawrence B. Smart (Tree Genetics & Genomes, 2012)

Over-expression of snakin-2 and extensin-like protein genes restricts pathogen invasiveness and enhances tolerance to Clavibacter michiganensis subsp. michiganensis in transgenic tomato (Solanum lycopersicum) - Vasudevan Balaji; Christine D. Smart (Transgenic Research, 2012)

Production of liver preneoplasia and gallbladder agenesis in turkey fetuses administered diethylnitrosamine - Gary M. Williams; Klaus D. Brunnemann; Michael J. Iatropoulos; Daniel J. Smart; Harald G. Enzmann (Archives of Toxicology, 2011)

Interpreting spatial language in image captions - Mark M. Hall; Philip D. Smart; Christopher B. Jones (Cognitive Processing, 2011)

Quantitative resistance to late blight from Solanum berthaultii cosegregates with R Pi-ber : insights in stability through isolates and environment - Gilda Rauscher; Ivan Simko; Hilary Mayton; Merideth Bonierbale; Christine D. Smart; Niklaus J. Grünwald; Andrew Greenland; William E. Fry (Theoretical and Applied Genetics, 2010)

Analysis of Biomass Composition Using High-Resolution Thermogravimetric Analysis and Percent Bark Content for the Selection of Shrub Willow Bioenergy Crop Varieties - Michelle J. Serapiglia; Kimberly D. Cameron; Arthur J. Stipanovic; Lawrence B. Smart (BioEnergy Research, 2009)

Quantitative Genetics of Traits Indicative of Biomass Production and Heterosis in 34 Full-sib F1 Salix eriocephala Families - Kimberly D. Cameron; Ingrid S. Phillips; Richard F. Kopp; Timothy A. Volk; Charles A. Maynard; Lawrence P. Abrahamson; Lawrence B. Smart (BioEnergy Research, 2008)

Characterization and mapping of R Pi-ber , a novel potato late blight resistance gene from Solanum berthaultii - G. M. Rauscher; C. D. Smart; I. Simko; M. Bonierbale; H. Mayton; A. Greenland; W. E. Fry (Theoretical and Applied Genetics, 2006)

Isolation of genes predominantly expressed in guard cells and epidermal cells of Nicotiana glauca - Lawrence B. Smart; Kimberly D. Cameron; Alan B. Bennett (Plant Molecular Biology, 2000)

Bacterial adsorption to thermoresponsive polymer surfaces - D. Cunliffe; C.A. Smart; J. Tsibouklis; S. Young; C. Alexander; E.N. Vulfson (Biotechnology Letters, 2000)

The return ofPhytophthora infestans, a potato pathogen that just won't quit - William E. Fry; Christine D. Smart (Potato Research, 1999)

Effect of phosphorus supply on periplasmic protein profiles in Rhizobia - J. B. Smart; M. J. Dilworth; A. D. Robson (Archives of Microbiology, 1984)

Effect of phosphorus supply on phosphate uptake and alkaline phosphatase activity in Rhizobia - J. B. Smart; M. J. Dilworth; A. D. Robson (Archives of Microbiology, 1984)

A continuous culture study of the phosphorus nutrition of Rhizobium trifollii WU95, Rhizobium NGR234 and Bradyrhizobium CB756 - J. B. Smart; A. D. Robson; M. J. Dilworth (Archives of Microbiology, 1984)